Analisis Jual Beli Hak Cipta Dalam Perspektif Hukum Pidana Islam Dan Undang-Undang Nomor 28 Tahun 2014 - Ghurrotul Muhajjalah; Nasiri . (STAI Syaichona Moh. Cholil Bangkalan, 2019)
This study aims to seek legal certainty from the practice of buying and selling copyright that occurs in society. By emphasizing the study of the point of view of Islamic criminal law in answering the legality of the practice of buying and selling copyright logically and comprehensively. Next, do a deeper analysis and study of the ratio legislation of Law No. 28 of 2014 concerning Copyright. The design of this study is normative legal research with a statute approach and comparative approach. Data collection techniques used documentation in the form of library studies with sources of legal material. The results of this study indicate that: 1) copyright is a new term that is still unfamiliar in the context of Islamic criminal law. Although its application has been indirectly recognized since the time of the Prophet with the necessity to include the name of the author in each of the writings cited. This is true on the basis of copyright ownership of property ownership. So that related to the legality of copyright sale and purchase transactions are answered on the basis of the legality of buying and selling in general. The difference is that the object (mauqud aih alaih) of copyright sale and purchase is based on the perspective of f urf contained in the criteria of the benefits of goods (muntafa’bih) which are maqsu and ‘urfan or in other words the public has economic value and is worth trading. 2) Copyright sale and purchase transactions are transactions that have been legalized for a long time in positive law in Indonesia. This is based on the existence of related rights in the exclusive rights inherent in a creator. The related rights are in the form of economic and moral rights. In the end, these economic rights are the basis of the legality and royalties generated from copyright sale and purchase transactions based on the legality of other transactions listed in Article 9 paragraph (1) of Law No. 28 of 2014 concerning copyright.